2019
DOI: 10.1155/2019/8175689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonuniform Fiber Geometries on the Microstructural Fracture Behavior of Ceramic Matrix Composites

Abstract: Microstructural fracture behavior of a ceramic matrix composite (CMC) with nonuniformly distributed fibers is studied in the presentation. A comprehensive numerical analysis package to study the effect of nonuniform fiber dimensions and locations on the microstructural fracture behavior is developed. The package starts with an optimization algorithm for generating representative volume element (RVE) models that are statistically equivalent to experimental measurements. Experimentally measured statistical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…They revealed that the periodic model would be used to predict effective performance, but the random model must be considered for local damage processes such as interface debonding or macroscopic matrix cracks. Random distribution and aggregation of fibres caused obvious stress concentration, which affected the predicted results of the transverse tensile properties of fibre-reinforced composites [7,8]. Fully characterising the actual microstructure of fibre-reinforced composite materials benefited the failure behavior simulation more accurately (Carl R et al [9], Romanov V et al [10]).…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the periodic model would be used to predict effective performance, but the random model must be considered for local damage processes such as interface debonding or macroscopic matrix cracks. Random distribution and aggregation of fibres caused obvious stress concentration, which affected the predicted results of the transverse tensile properties of fibre-reinforced composites [7,8]. Fully characterising the actual microstructure of fibre-reinforced composite materials benefited the failure behavior simulation more accurately (Carl R et al [9], Romanov V et al [10]).…”
Section: Introductionmentioning
confidence: 99%